2012
DOI: 10.1016/j.cogdev.2011.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Pointing disrupts preschoolers’ ability to discriminate between knowledgeable and ignorant informants

Abstract: By 4 years of age, children have been reinforced repeatedly for searching where they see someone point. In two studies, we asked whether this history of reinforcement could interfere with young children’s ability to discriminate between a knowledgeable and an ignorant informant. Children watched as one informant hid a sticker while another turned around, and then both informants indicated where they though the sticker was, either by pointing or by using a less practiced means of reference. Children failed to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 28 publications
0
31
0
Order By: Relevance
“…Indeed, research has shown that the pointing gesture is an important indicator of another person's knowledge state for younger children, regardless of the person's verbal indication (Grassmann & Tomasello, 2010) or visual access (Palmquist, Burns, & Jaswal, 2012;. Nevertheless, as mentioned previously, past research seems to indicate that the total number of pointing gestures did not influence the consensus effect.…”
Section: Discussionmentioning
confidence: 86%
“…Indeed, research has shown that the pointing gesture is an important indicator of another person's knowledge state for younger children, regardless of the person's verbal indication (Grassmann & Tomasello, 2010) or visual access (Palmquist, Burns, & Jaswal, 2012;. Nevertheless, as mentioned previously, past research seems to indicate that the total number of pointing gestures did not influence the consensus effect.…”
Section: Discussionmentioning
confidence: 86%
“…In the absence of conflicting evidence, 3‐year‐olds trust previously inaccurate informants in an object‐labeling task (Vanderbilt, Heyman, & Liu, ) and even follow the advice of a communicator who is labeled as a “big liar” despite receiving continuous feedback by the experimenter (Mascaro & Sperber, ). It is especially difficult for children not to follow pointing gestures in standard object choice paradigms as informative pointing gestures are generally not only produced with clear communicative intent (Heyman, Sritanyaratana, & Vanderbilt, ) but also have a veridical history (Palmquist et al., ). For example, 3‐year‐olds are unable to ignore a clearly ignorant pointer's gesture directly conflicting with a reliable gesture from a knowledgeable communicator when presented simultaneously (Palmquist, Burns, & Jaswal, ; Palmquist & Jaswal, ).…”
Section: Discussionmentioning
confidence: 99%
“…It is especially difficult for children not to follow pointing gestures in standard object choice paradigms as informative pointing gestures are generally not only produced with clear communicative intent (Heyman, Sritanyaratana, & Vanderbilt, ) but also have a veridical history (Palmquist et al., ). For example, 3‐year‐olds are unable to ignore a clearly ignorant pointer's gesture directly conflicting with a reliable gesture from a knowledgeable communicator when presented simultaneously (Palmquist, Burns, & Jaswal, ; Palmquist & Jaswal, ). They also appear unable to ignore pointing gestures to one of two containers even if these points are constantly misleading in several consecutive trials (Couillard & Woodward, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, regardless of whether the informant actually saw the baiting event or not, children relied to the same extent on both persons when they were pointing to convey information. Palmquist, Burns, and Jaswal (2012) also showed that this effect is unique for pointing CONFLICTING SOCIAL CUES 45 and does not occur for other referential forms. Taken together, these considerations and studies provide evidence that for preschool children, the pointing gesture is an important indicator of another person's referential intention and his knowledge state, regardless of the person's visual access, which has previously been considered the strongest indicator of a person's knowledge (cf.…”
mentioning
confidence: 84%